Influence of welding parameters on weld bead in laser arc hybrid welding process using coaxial monitoring system and image processing. (May 2014) - Kim, T. W.; Park, Y. W.
Abstract : The productivity and weld quality of a welding process are closely related to the cost and reliability of the end products. A laser arc hybrid welding process can be used to improve the two significant factors because one welding process compensates for the disadvantages of the other welding process. In this research, a coaxial weld monitoring system for laser arc hybrid welding was designed using a complementary metal oxide semiconductor (CMOS) camera. The optical components were optimised to obtain reliable images. Experiments with varying laser power, welding speed, and arc current were carried out while real time images were captured. The bead width was extracted from the images using image processing and a median filter. The analysis of variation technique was then used to identify the influence of the process variables on the bead width and to verify the monitoring system.